Active Learning and CDIO Implementation in Colombia (2013)
In this paper we discuss common problems in Colombian universities in regard to engineering professional programs. We also discuss the reasons to implement a curriculum reform following the CDIO model at Icesi University, and present some preliminary results of implementing this reform, mainly concerning student motivation and attrition reduction The adoption of CDIO model is aimed not only to offer a integral engineering education, increase the quality of our programs, establishing a cycle of continuous improvement and also to encourage students by offering a challenging curriculum that focuse s its professional component on solving engineering problems.